Defects in ankyrin-based membrane protein targeting pathways underlie atrial fibrillation - Cunha, Shane R.; Hund, Thomas J.; Hashemi, Seyed; Voigt, Niels; Li, Na; Wright, Patrick; Koval, Olha; Li, Jingdong; Gudmundsson, Hjalti; Gumina, Richard J.; Karck, Matthias; Schott, Jean-Jacques; et al. (Circulation, 2011)
Background— - - Atrial fibrillation (AF) is the most common cardiac arrhythmia, affecting >2 million patients in the United States alone. Despite decades of research, surprisingly little is known regarding the molecular pathways underlying the pathogenesis of AF. ANK2 encodes ankyrin-B, a multifunctional adapter molecule implicated in membrane targeting of ion channels, transporters, and signaling molecules in excitable cells. - - Methods and Results— - - In the present study, we report early-onset AF in patients harboring loss-of-function mutations in ANK2. In mice, we show that ankyrin-B deficiency results in atrial electrophysiological dysfunction and increased susceptibility to AF. Moreover, ankyrin-B+/− atrial myocytes display shortened action potentials, consistent with human AF. Ankyrin-B is expressed in atrial myocytes, and we demonstrate its requirement for the membrane targeting and function of a subgroup of voltage-gated Ca2+ channels (Cav1.3) responsible for low voltage-activated L-type Ca2+ current. Ankyrin-B is associated directly with Cav1.3, and this interaction is regulated by a short, highly conserved motif specific to Cav1.3. Moreover, loss of ankyrin-B in atrial myocytes results in decreased Cav1.3 expression, membrane localization, and function sufficient to produce shortened atrial action potentials and arrhythmias. Finally, we demonstrate reduced ankyrin-B expression in atrial samples of patients with documented AF, further supporting an association between ankyrin-B and AF. - - Conclusions— - - These findings support that reduced ankyrin-B expression or mutations in ANK2 are associated with AF. Additionally, our data demonstrate a novel pathway for ankyrin-B-dependent regulation of Cav1.3 channel membrane targeting and regulation in atrial myocytes.